Diode Green Laser in the Lid Trichiasis Treatment - Raquel Galvão Bezerra; Roberta Lílian Fernandes de Sousa Meneghim; Carlos Roberto Padovani; Silvana Artioli Schellini (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To validate the standard values and evaluate the success rate in the treatment of minor and major trichiasis using thermoablation with a diode green laser. Methods: In this interventional prospective study, individuals with minor or major trichiasis who were treated with thermoablation using diode green laser were included. The patients' mean age was 72.1 years; the majority were females (54.1%) and Caucasian (98%). The parameters of the diode laser were wavelength of 532 nm, application time of 200 ms, target size of 50 μm, interval between the shots 150 to 200 ms, and power of 600 to 750 mW. The number of shots was defined by the depth of ablation sufficient to reach the pilus hair bulb. The patients were evaluated by slit-lamp every 3 to 4 months, for up to 15 months. The treatment success rate and the association between variables were analyzed. Results: The study sample was comprised of 98 patients with 135 affected lids and 337 lashes with trichiasis. Minor trichiasis (91.8%), unilateral trichiasis (67.3%), trichiasis affecting the lower eyelid (85.9%), and trichiasis resulting from blepharitis (64.3%) were the most common presentation profiles. The overall cure rate at the end of the study was 85%, with 69% being cured with a single session and 82.8% with two treatment sessions. Conclusion: Thermoablation using a diode green laser applying the specified parameters to treat minor and major trichiasis is effective and results in high cure rate.